Implementación de un sistema de producción modular para la fábrica de construcciónes industriales INCATELL de la ciudad de Riobamba. - Tello Santillán, Mauricio Rafael (2011)
This project has an objective the comparative analysis of a system of conventional production with a system of modular production in the garment factory industrial "INCATELL" from the city of Riobamba. To perform this comparison were analyzed some of the most important characteristics of the two systems such as personnel, machinery, used space, training, working environment, incentive system, quality, cycle time, efficiencies and delivery times, so to be able to demonstrate which of these two systems is the most convenient.